2019
DOI: 10.1111/ctr.13510
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between anti‐infective agents and immunosuppressants—Guidelines from the American Society of Transplantation Infectious Diseases Community of Practice

Abstract: These updated guidelines from the Infectious Diseases Community of Practice of the American Society of Transplantation provide an update on potential drug‐drug interactions between anti‐infectives and immunosuppressants, which are most notable with calcineurin and mTOR inhibitors. Drug‐drug interactions may occur through pharmacokinetic mechanisms leading to altered drug concentrations of either the anti‐infective or immunosuppressive drug, or by pharmacodynamic interactions increasing or decreasing the effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 92 publications
0
34
0
Order By: Relevance
“…Rifampicin significantly decreases level of CNI and mTORi which might result in allograft rejection. 20,21 Among three patients who had rejection after diagnosis of TB, only one developed allograft rejection at 19 days with evidence of sub therapeutic cyclosporine level. This represented 4% incidence of potential rifampicin associated allograft rejection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rifampicin significantly decreases level of CNI and mTORi which might result in allograft rejection. 20,21 Among three patients who had rejection after diagnosis of TB, only one developed allograft rejection at 19 days with evidence of sub therapeutic cyclosporine level. This represented 4% incidence of potential rifampicin associated allograft rejection.…”
Section: Discussionmentioning
confidence: 99%
“…3 Management of TB in transplant recipients is challenging as anti-tuberculosis agents have significant interaction with immunosuppressants and the disease contains high mortality up to 40%. 3,4 Incidence of post-transplant TB varies among countries and types of transplanted organ. Overall incidence in kidney transplant (KT) recipients was 1.69%, however, the number was reported as high as 15% in high endemic country.…”
Section: Introductionmentioning
confidence: 99%
“…This triazole drug may induce visual disturbances, as well as hepatotoxicity and phototoxicity events in CF patients [52,53]. In addition, its concomitant use with immunosuppressants in solid organ transplant recipients needs careful evaluation of serum level of the immunosuppressant [54]. Importantly, the demonstrated MIC values for ARF mirror the achievable blood levels following an oral or parenteral dose of ARF (maximum plasma concentration: 0.68 ± 0.45 μg/ ml).…”
Section: Discussionmentioning
confidence: 99%
“…In one study, contraindicated DDIs were reported in nearly 25% of inpatients prescribed mold-active triazoles [ 56 ]. Many of the novel therapeutics in hematology-oncology and drugs used for maintenance of immunosuppression in SOT patients also have clinically actionable DDIs with triazoles [ 57 , 58 ]. These interactions may require the monitoring of serum levels and/or dose adjustments.…”
Section: Multidisciplinary Collaborationmentioning
confidence: 99%